Personalistika a budoucnost sociálních sítí v ČR - Böhmová, Lucie; Pavlíček, Antonín (Univerzita Pardubice, 2013)
The article is focused on social networks development in the Czech Republic and their influence on HR in organizations during the process of recruitment. The aim is to research, if the social networks could replace job boards as jobs.cz, prace.cz etc. Next aim of the thesis is to compare the form - how the companies offer new/vacant jobs on internet. Another focus is to discover how the HR specialists evaluate the use of social networks to help the recruitment of new employees and what their experience with this way of recruiting is.
Human resurces and future of social networks in the Czech Republic
Keywords: human resources; social networks; job boards; recruitment